Spatio-temporal variability of processes across Antarctic ice-bed–ocean interfaces - Colleoni, Florence; De Santis, Laura; Siddoway, Christine S.; Bergamasco, Andrea; Golledge, Nicholas R.; Lohmann, Gerrit; Passchier, Sandra; Siegert, Martin J. (Nature communications, 2018)
Understanding how the Antarctic ice sheet will respond to global warming relies on knowledge of how it has behaved in the past. The use of numerical models, the only means to quantitatively predict the future, is hindered by limitations to topographic data both now and in the past, and in knowledge of how subsurface oceanic, glaciological and hydrological processes interact. Incorporating the variety and interplay of such processes, operating at multiple spatio-temporal scales, is critical to modeling the Antarctic’s system evolution and requires direct observations in challenging locations. As these processes do not observe disciplinary boundaries neither should our future research. Understudied in the Antarctic system are the subsurface interfaces between ice-sheet, ocean and geological substrate. Here, the authors review our understanding of these components and propose new avenues of holistic dynamic modeling to achieve a unified understanding of past, present and future polar climate.